Effect of Biopesticide Gamak Leaf Extract on Jabon Caterpillar Pest Mortality (Arthroschista hilaralis) in White Jabon Plants (Anthocephalus cadamba Miq) - Juniaty Arruan Bulawan; Fardyansyah Hasan; Wawan Irawan Kadir (Universitas Sembilanbelas November Kolaka, 2017)
White Jabon (Anthochepalus cadamba Miq). is one of the tree species that has high prospects for industrial plantations and reforestation (greening) in Indonesia because it has very fast growth, very good adaptability. Disorders of plant disturbance organisms most commonly found in Jabon, Jabon caterpillar (Arthroschista hilaralis) become a major problem that can reduce the quality and quantity of wood. Pest control with chemicals does not provide maximum results so it is necessary to test with biopesticides. The study to examine the effect of gamal leaf extract as a natural insecticide was carried out using a completely randomized design with four treatments, namely the concentration of gamal leaf extract 0% (P0), 50% (P1), 75% (P2), 100% (P3). The results showed that gamal leaf extract as a vegetable insecticide had a positive effect on the mortality of A. hilaralis larvae in Jabon plants. The higher the concentration of gamal leaf extract, the higher the mortality rate in A. hilaralis larvae. This can be seen in the most effective concentration is the concentration of 100% with a mortality rate of 95%. The highest total mortality of A. hilaralis larvae occurred at a concentration of 100% ie 2.1 head / day. The higher the concentration of gamal leaf extract, the higher the speed of death of the larvae